A Floating Optical Buoy (FOBY) for Direct Measurement of Water‐Leaving Radiance Based on the Skylight‐Blocked Approach (SBA): An Experiment in Honghu Lake, China. Issue 10 (22nd October 2020) - Tian, Liqiao; Li, Sen; Li, Yong; Sun, Zhaohua; Song, Qingjun; Zhao, Jun
Abstract: Water‐leaving radiance ( L w ), or remote sensing reflectance ( R rs ), is a fundamental parameter of water color remote sensing. However, obtaining accurate and precise measurements of L w is quite challenging. This study is intended to illustrate the design and implementation of a novel floating optical buoy (FOBY) to measure L w directly in the field based on the skylight‐blocked approach (SBA). To assess the performance of FOBY, an experiment was conducted in Honghu Lake, China, a typical shallow turbid lake. FOBY‐derived R rs can characterize the spectral features of different water types including water with kelp as substrate, relatively high chlorophyll‐a contents, and high amounts of suspended sediment (SS). FOBY‐derived R rs is superior to that from a portable spectroradiometer (PSR 3500+, Spectral Evolution Inc.) based on the conventional above‐surface approach (ASA) in terms of data quality and stability. FOBY measurements had a quality assurance score (QAS) of 0.98 and a mean coefficient of variation (CV) of 3.6–7.0%, while the mean CV for PSR measurements is more than 2 times larger than that of FOBY in the visible domain. The measurement uncertainties may result from self‐shading, sensor tilt, and the immersed depth of the cone (IDC), which deserve further investigations. In the future, long‐term continuous floating observations of different aquatic environments can be conducted using the instrument with well‐refined data quality control. Plain Language Summary: Aimed at accurate and precise in situ measurements of water‐leaving radiance ( L w ) or remote sensing reflectance ( R rs ), a floating optical buoy (FOBY) was developed to measure L w directly based on the skylight‐blocked approach in this paper. An experiment was conducted in Honghu Lake, China. Our results demonstrated less variability of R rs from FOBY than from the traditional above‐surface approach. On the other hand, it should be noted that uncertainties of R rs from FOBY still exist and deserve further investigations. In the future, FOBY can serve for long‐term continuous observations of different aquatic environments with well‐refined data quality control. Key Points: A floating optical buoy (FOBY) designed to measure water‐leaving radiance directly based on the skylight‐blocked approach was developed FOBY‐derived remote sensing reflectance showed better performance than that from a PSR in terms of data quality and stability The uncertainties of FOBY‐derived R rs may result from self‐shading, sensor tilt, and the immersed depth of the cone (IDC)